THE ANALYSIS OF TIDAL CURRENT IN SURAMADU BRIDGE PIER FOR MARINE POWER GENERATION TEST SITE - R. Bambang Adhitya Nugraha; Erwandi Erwandi; Hendry Syahputra; La Ode Nurman Mbay (Pusat Riset Kelautan, 2018)
Recently, the interest in renewable ocean energy has been growing rapidly among the ocean researchers in Indonesia. In this paper, the pattern of tidal current in Madura Strait was analyzed and it is used as First we present the general information of the structure of Suramadu Bridge and explain the purpose of installing tidal current turbine between its piers. Second, we develop the numerical model of Madura Strait. The bottom topography of Madura Strait is digitized from bathymetry map produced by Indonesian Navy. A nested hydrodynamic model has been developed to refine the specific area of interest around the piles of the Suramadu Bridge. MIKE-21 program is then employed to simulate the tidal current that passes between the piles of the bridge. Next, we validate the model by conducting the field measurement of the speed of tidal current between pile no. 56 and pile no. 57. We deployed ADCP and measured the current speed for 15 days. The obtained data is then compared with the numerical model. The results show that the simulated currents has similar pattern with the measured data. We also discuss the characteristics of the simulated tidal current comparing with the ADCP results. Finally we estimate the possible produced power produced from the kinetic energy of the predicted tidal current of hydrodynamic.